2015
DOI: 10.1097/ftd.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Evaluation of the Thermo Scientific Prelude for Measurement of Immunosuppressant Drugs Using Sample Preparation Liquid Chromatography–Tandem Mass Spectrometry

Abstract: Immunosuppressant drugs (ISDs) are commonly prescribed to solid organ transplant patients. Their narrow therapeutic index and potential for toxicity necessitates careful monitoring of blood concentrations. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) methods are increasingly used for ISD measurement. However, there remain many challenges with this methodology, particularly regarding interassay variability. The Thermo Scientific Prelude is an online extraction/liquid chromatography platform that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The largest mean difference from the reference measurement (exact matching-isotope dilution MS) was 4.4% [52]. A unified method by Thermo Fisher's Prelude online extraction and LC system coupled to a TSQ Vantage MS platform was evaluated for measuring cyclosporine A, tacrolimus, and sirolimus by 3 hospital labs [53]. The site bias for each immunosuppressant was calculated against the multisite mean.…”
Section: Commercialization and Standardization Of Lc-ms/ms Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest mean difference from the reference measurement (exact matching-isotope dilution MS) was 4.4% [52]. A unified method by Thermo Fisher's Prelude online extraction and LC system coupled to a TSQ Vantage MS platform was evaluated for measuring cyclosporine A, tacrolimus, and sirolimus by 3 hospital labs [53]. The site bias for each immunosuppressant was calculated against the multisite mean.…”
Section: Commercialization and Standardization Of Lc-ms/ms Methodsmentioning
confidence: 99%
“…Lastly, a fourth group found that differences in hematocrit (20% to 45%), spotted blood volume (25,35,50,75, and 100 μL), and punch location did not affect immunosuppressant quantitation [39]. [46,47] Online solid phase extraction (analytical run time of 1 min) [48] No LC separation (analytical run time of 13 s) [49] Liquid handler [50] Commercialization/ Standardization 7-Lab tacrolimus unification [52] 3-Lab cyclosporine A, tacrolimus, and sirolimus unification [53] Much of these DBS validation studies involve the deposition of venous blood from a collection tube onto the paper. Two recent studies evaluated capillary blood from a finger stick.…”
Section: Non-traditional Sample Types For Lc-ms/ms Analysismentioning
confidence: 98%
“…Evaluations of LC–MS/MS for commercially available immunosuppressant assays have also been reported . Peake et al reported a multicenter evaluation of Thermo Fisher's Prelude for the measurement of CsA, TAC, and SIR. A unified method by the Prelude online extraction and LC system coupled to a TSQ Vantage MS platform was evaluated in 3 hospital laboratories.…”
Section: Chromatography Methodsmentioning
confidence: 99%
“…55,56 Levine et al 55 Evaluations of LC-MS/MS for commercially available immunosuppressant assays have also been reported. [57][58][59]…”
Section: Standardization and Commercializationmentioning
confidence: 99%
“…589 The sensitivity and selectivity provided by MS helped to ease sample preparation in clinical chemistry laboratories. Column-switching systems coupling the extraction support to the chromatographic column before MS detection were also used for the analysis of sirolimus [598][599][600][601][602][603][604][605][606][607][608][609][610][611] and everolimus 598,599,602,603,[605][606][607]609,[612][613][614] in whole blood. LLE 615 or SPE 616 on 96-well plates constitutes another approach for sample preparation automatisation.…”
Section: Mtor Inhibitorsmentioning
confidence: 99%